Immunocytochemical p63 expression discriminates between primary cutaneous follicle centre cell and diffuse large B cell lymphoma‐leg type, and is of the TAp63 isoform. Issue 1 (1st March 2016) - Robson, Alistair; Shukur, Zena; Ally, Mina; Kluk, Justine; Liu, Kun; Pincus, Laura; Sahni, Debjani; Sundram, Uma; Subtil, Antonio; Karai, Laszlo; Kempf, Werner; Schieke, Stefan; et al.
Abstract : Aims: The p63 gene shares structural and functional homologies with the p53 family of transcriptional activators, but differs in exhibiting a consistent expression pattern in normal tissues. Although p63 is rarely mutated in malignancy studies of primary human tumours and cell lines suggest that p63 may promote tumour development. In non‐Hodgkin's nodal lymphoma, TAp63 expression in follicular lymphoma (54%) and diffuse large B cell lymphoma (34%) has been described and correlated with the proliferative index. In this study, we analysed a series of primary cutaneous B cell lymphomas for immunohistochemical expression of p63. Methods and results: Thirty cases of diffuse large B cell lymphoma leg type (pcDLBCLL) and 34 cases of follicle centre cell lymphoma (pcFCCL) were stained using a generic antibody to p63, and a subset of these with an antibody specific for delta‐Np63 isoform. The results indicate a significant difference between pcDLBCLL (21 of 30) and pcFCCL (four of 34) in p63 expression ( P  = 0.000); expression correlated strongly with the proliferation rate as assessed by Ki‐67 ( P  = 0.015). None of the p63 (+) cases tested expressed the delta‐Np63 isoform, suggesting that expression is of the TAp63 isoform. Conclusions: Functional studies are required to clarify the significance of p63 overexpression in primary cutaneous B cell lymphoma.